Nonlinear numerical parametric study of the number and arrangement of dowels connecting the wall to the bounding frame for the seismic strengthening of RC frames with RC infill walls - Georgiou, Elpida; Kyriakides, Nicholas; Chrysostomou, Christis (My University, 2022)
The seismic retrofitting of existing multi-storey multi-bay reinforced concrete (RC) frame buildings by the conversion of selected bays into new RC infilled walls is the subject of this research work. The contribution of dowels that connect a new RC infill wall to the surrounding existing RC frame members was studied through a parametric study. The parametric study was performed by nonlinear response-history analyses of a finite element (FE) model. A two-dimensional (2D) frame was modeled, and analyses were performed to calibrate it using the experimental results obtained from a full-scale experiment. The description of the experiment, the experimental results, and the FE model simulation of the test specimen are presented in Georgiou et al. (2018), Georgiou et al. (2022) and Kyriakides et al. (2015) along with a comparison between the experimental results and the numerical ones. Based on the experimental results it was concluded that the number of dowels used in the experiment resulted in a monolithic behavior of the RC infilled frame. To complement the experimental results and to study the interaction between RC infills and the bounding frame both at the global and local level, a parametric study was performed by reducing the number of dowels starting from a spacing of 100 mm (monolithic) to no dowels. The numerical results of the parametric study show that the number of dowels used in the experimental study can be reduced significantly making the use of this method more attractive. These results also provide a basis for the development of a general model for the design of RC infills in existing RC frames, particularly regarding the connection details of the new RC infill walls to the existing bounding frame. The parametric study of the number of dowels connecting the wall to the bounding frame is presented and conclusions are drawn regarding, among others, the effect on the stiffness of the frame, the top storey displacement, the base shear, the axial and shear forces in the dowels, as well as the bending moment at the base of the wall and the outer columns. Some observations that can lead to design recommendations are also presented.
Keywords: Retrofitting seismic deficient structures; RC infill walls; Modelling of dowels; Finite element model; Nonlinear numerical parametric study